Usefulness of Urea as a Means of Improving the Solubility of Poorly Water-Soluble Ascorbyl Palmitate - Inoue, Yutaka (Int J Med Chem, 2017)
The aim of this study was to evaluate complexes of L-ascorbyl palmitate (ASCP) and urea (UR). This evaluation involved differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), near-infrared spectroscopy (NIR), a solubility test, a 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging test, and a mushroom tyrosinase inhibition assay. Physicochemical evaluation revealed that ASCP/UR complexes form at a molar ratio of 1/12. The solubility test revealed that ASCP/UR complexes had increased solubility compared to ASCP. The DPPH radical scavenging test and mushroom tyrosinase inhibition assay revealed that the activity of ASCP/UR complexes was not impaired by complex formation. These results are probably due to the tetragonal crystal system of UR changing to a hexagonal crystal system and interaction with the alkyl group of ASCP.